Luteolin Induces Selective Cell Death of Human Pluripotent Stem Cells - Young-Hyun Go; Jumee Kim; Ho-Chang Jeong; Seong-Min Kim; Yun-Jeong Kim; Soon-Jung Park; Sung-Hwan Moon; Hyuk-Jin Cha (Biomedicines, 2020)
Despite recent advances in clinical stem cell therapy applications based on human pluripotent stem cells (hPSCs), potential teratoma formation due to the presence of residual undifferentiated hPSCs remains a serious risk factor that challenges widespread clinical application. To overcome this risk, a variety of approaches have been developed to eliminate the remaining undifferentiated hPSCs via selective cell death induction. Our study seeks to identify natural flavonoids that are more potent than quercetin (QC), to selectively induce hPSC death. Upon screening in-house flavonoids, luteolin (LUT) is found to be more potent than QC to eliminate hPSCs in a p53-dependent manner, but not hPSC-derived smooth muscle cells or perivascular progenitor cells. Particularly, treating human embryonic stem cell (hESC)-derived cardiomyocytes with LUT efficiently eliminates the residual hESCs and only results in marginal effects on cardiomyocyte (CM) functions, as determined by calcium influx. Considering the technical limitations of isolating CMs due to a lack of exclusive surface markers at the end of differentiation, LUT treatment is a promising approach to minimize teratoma formation risk.